The Effect of Leverage Ratio, Activity Ratio and Sales Growth Ratio on Financial Performance on Food and Beverage Sub Sector Companies 2017-2021 - Hasanuddin (TRIGIN PUBLISHER, 2022)
This study aims to determine the effect of the measured variable with leverage (DER), Activity (TATO), Growth (SG) on Financial Performance (ROA) Manufacture company food and beverage sector registered in the Indonesian Capital Market for the period2017-2021.The population of this company is 70 food and beverage companies that have been registered in the Indonesian Capital Market in 2017-2021. The sampling technique or method used is purposive sampling by obtaining a sample of 14 companies. This study uses secondary data, such as financial statements that have been fulfil criteria, financial statements obtained from the Indonesian Capital Market which can be accessed through www.idx.co.id.One of the analytical techniques used in this research is linear regression of panel data and using the EViews program. The results of this study show that the Leverage Ratio (DER) and Sales Growth Ratio (SG) have a significant positive effect, the Activity Ratio (TATO) has a positive but not significant effect.